Challenges and Strategies of a Private English Tutor in Teaching Autistic Children:: A Case Study - Hafizhotunnissa Tabroni, Fitri Maghvira; Gozali, Agus (International Journal of Language Teaching and Education, 2026)
Private English tutoring for children with Autism Spectrum Disorder (ASD) has received little attention in the field of inclusive education, even though its role is becoming increasingly relevant as a supportive alternative to formal schooling. This study aims to identify the challenges and strategies of a private English tutor in teaching children with ASD using an intrinsic qualitative case study approach, with data collected through semi-structured interviews, observations, and document analysis. The findings indicate that communication difficulties, a preference for routines, repetitive behaviors, and context-inappropriate behaviors each present challenges that the tutor must address independently without institutional support. In response, the tutor developed strategies such as visual aids, student-interest-based materials, structured routines, real-time instructional adjustments, and positive reinforcement. This study underscores the need for inclusive teacher training programs that reflect the realities of teaching English to students with ASD outside formal institutions.